Occupational exposure to solvents and risk of head and neck cancer in women: a population-based case–control study in France. Issue 1 (9th January 2017) - Carton, Matthieu; Barul, Christine; Menvielle, Gwenn; Cyr, Diane; Sanchez, Marie; Pilorget, Corinne; Trétarre, Brigitte; Stücker, Isabelle; Luce, Danièle
Abstract : Objective: Our objective was to investigate the association between head and neck cancer and occupational exposure to chlorinated, oxygenated and petroleum solvents in women. Methods: Investigation of occupational and environmental CAuses of REspiratory cancers (ICARE), a French population-based case–control study, included 296 squamous cell carcinomas of the head and neck (HNSCC) in women and 775 female controls. Lifelong occupational history was collected. Job-exposure matrices allowed to assess exposure to 5 chlorinated solvents (carbon tetrachloride; chloroform; methylene chloride; perchloroethylene; trichloroethylene), 5 petroleum solvents (benzene; special petroleum product; gasoline; white spirits and other light aromatic mixtures; diesel, fuels and kerosene) and 5 oxygenated solvents (alcohols; ketones and esters; ethylene glycol; diethyl ether; tetrahydrofuran). OR and 95% CIs, adjusted for smoking, alcohol drinking, age and geographical area, were estimated with logistic models. Results: Elevated ORs were observed among women ever exposed to perchloroethylene (OR=2.97, 95% CI 1.05 to 8.45) and trichloroethylene (OR=2.15, 95% CI 1.21 to 3.81). These ORs increased with exposure duration (OR=3.75, 95% CI 0.64 to 21.9 and OR=4.44, 95% CI 1.56 to 12.6 for 10 years or more, respectively). No significantly increased risk of HNSCC was found for occupational exposure to the other chlorinated, petroleum or oxygenated solvents. Conclusions: These findings suggest that exposure to perchloroethylene or trichloroethylene may increase the risk of HNSCC in women. In our study, there is no clear evidence that the other studied solvents are risk factors for HNSCC.